Recent advances in nano-enabled agriculture for improving plant performance - Wu, Honghong; Li, Zhaohu (The Crop journal, 2022)
Nano-enabled agriculture is an emerging hot topic. To facilitate the development of nano-enabled agriculture, reviews addressing or discussing the applications, knowledge gap, future research needs, and possible new research field of plant nanobiotechnology in agricultural production are encouraged. Here we review the following topics in plant nanobiotechnology for agriculture: 1) improving stress tolerance, 2) stress sensing and early detection, 3) targeted delivery and controlled release of agrochemicals, 4) transgenic events in non-model crop species, and 5) seed nanopriming. We discuss the knowledge gaps in these topics. Besides the use of nanomaterials for harvesting more electrons to improve photosynthetic performance, they could be used to convert nIR and UV to visible light to expand the light spectrum for photosynthesis. We discuss this approach to maintaining plant photosynthesis under light-insufficient conditions. Our aim in this review is to aid researchers to learn quickly how to use plant nanobiotechnology for improving agricultural production.